Sujetos deseantes: una aproximación teórica a las dinámicas del deseo gay - Pease Gálvez, Franklin (Pontificia Universidad Católica del Perú, 2024)
Understanding gay desire as a social phenomenon is a conceptual challenge. This essay was born as an attempt to put together a theoretical apparatus that allows us to understand the dynamics of desire of young upper-class gay men from Lima for a thesis project. Different currents are reviewed to approach this phenomenon: from gender studies and queer theory, to French postmodernism and poststructuralism. With these contributions, the conceptual tools necessary to explain the desiring dynamics will be developed. These are constituted by the construction of the object of desire from the process of subjectivation and the development of courtship strategies that respond to that desired object. It also considers how the positions that desiring subjects assume in the dynamics of desire influence their social position. Along these lines, the aim is to emphasize the productive nature of desire, the subversiveness of the queer experience and the relationship between the subject and the structure. This dissertation is not intended to be a determining or essentialist statement of the nature of homosexual desire, but rather to propose a way to understand the ways in which young gay people come to desire and be desired in an environment that is often adverse to them.

Entender el deseo gay como un fenómeno social es un reto conceptual. Este ensayo nace como un intento de armar un aparato teórico que permita aprehender las dinámicas del deseo de los jóvenes gays limeños de clase alta para un proyecto de tesis. Se revisan distintas corrientes para aproximarnos a este fenómeno: desde los estudios de género y la teoría queer, al posmodernismo y el posestructuralismo francés. Con estos aportes, se elaborarán las herramientas conceptuales necesarias para explicar las dinámicas deseantes. Estas se encuentran constituidas por la construcción del objeto de deseo a partir del proceso de subjetivación y el desarrollo de estrategias de cortejo que responden a ese objeto deseado. También se plantea cómo las posiciones que los sujetos deseantes asumen en las dinámicas de deseo se relacionan con su posición social. En esta línea, se pretende poner énfasis en lo productivo del deseo, lo subversivo de la experiencia queer y la relación entre el sujeto y la estructura. Esta disertación no pretende ser una declaración determinante ni esencialista de la naturaleza del deseo homosexual, sino que busca proponer una manera de comprender las maneras en que los jóvenes gays llegan a desear y ser deseados en un entorno que les es muchas veces adverso.
Desiring subjects: a theoretical approach to the dynamics of gay desire
Keywords: Desire; Gay; Sexuality; Subjectivities; Deseo; Gay; Sexualidad; Subjetividades; https://purl.org/pe-repo/ocde/ford#5.04.01